2015
DOI: 10.1007/s10661-015-4543-1
|View full text |Cite|
|
Sign up to set email alerts
|

Preconcentration and determination of lead and cadmium levels in blood samples of adolescent workers consuming smokeless tobacco products in Pakistan

Abstract: The present study was aimed to evaluate the cadmium (Cd) and lead (Pb) levels in the blood samples of adolescent boys, chewing different smokeless tobacco (SLT) products in Pakistan. For comparative purpose, boys of the same age group (12-15 years), not consumed any SLT products were selected as referents. To determine trace levels of Cd and Pb in blood samples, a preconcentration method, vortex-assisted liquid-liquid microextraction (VLLME) has been developed, prior to analysis by flame atomic absorption spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Five effect biomarkers were found to exceed normal limits, indicating potential kidney disorders. The table also demonstrates three scholarly publications Arain, et al (2015b) Cd levels in the hair of workers at the battery recycling: 2.12 ± 0.29 (μg/g) or over the normal limit…”
Section: Relationship Between CD Levels Biomarkers Of Exposure and Ef...mentioning
confidence: 89%
See 1 more Smart Citation
“…Five effect biomarkers were found to exceed normal limits, indicating potential kidney disorders. The table also demonstrates three scholarly publications Arain, et al (2015b) Cd levels in the hair of workers at the battery recycling: 2.12 ± 0.29 (μg/g) or over the normal limit…”
Section: Relationship Between CD Levels Biomarkers Of Exposure and Ef...mentioning
confidence: 89%
“…that discuss the relationship between Cd levels and effect biomarkers associated with kidney disorders among workers in the battery industry. These publications include studies by Gao et al (2016), Bot et al (2020), andArain et al (2015b). Among these, Bot et al (2020) reported that Cd levels in the body that exceed normal limits are associated with a subsequent increase in effect biomarkers beyond the usual range.…”
Section: Relationship Between CD Levels Biomarkers Of Exposure and Ef...mentioning
confidence: 99%
“…In IL-DLLME, the dispersion of solvent is usually assisted by an external organic solvent or by an additional energy such as shaking [27], vortexing [28], ultrasound [29], or heating [30]. The dispersive solvents, such as methanol or acetonitrile, usually in the mL range to create a cloudy solution of the extraction solvent.…”
Section: Introductionmentioning
confidence: 99%